Economic Prosperity in Maine: Held Back by the Lack of Higher Education - Trostel, Philip (Maine Policy Review, 2002)
Maine lags the nation in economic prosperity and in education attainment, and there is little doubt that the relative lack of higher education in Maine is a leading factor. In this article, Trostel looks at each of the three sources of Maine’s relatively low education attainment: the net emigration of college graduates (who are presumably in search of employment opportunities elsewhere); relatively fewer students going on to college; and the net emigration of high-school graduates leaving Maine to attend out-of-state postsecondary schools. While all three factors have happened in Maine to some extent, the net emigration of the state’s high-school students is by far the biggest factor explaining the low levels of education attainment. After analyzing some of the data related to public support for education and cost, Trostel concludes that higher education in Maine is not a good enough deal relative to other states to keep a high proportion of its traditional-aged, college-bound youth here. To reverse this trend, Trostel says Maine needs to lower tuition costs and substantially increase the quality of our higher education.
Keywords: Maine; higher education; post-secondary education